Modified PWM Technique For Torque Ripples Reduction In Three Phase PM BLDC Motors - Salah, Wael Abdel Muhdi Yacoup (2012)

(untitled)
Permanent magnet (PM) brushless DC motors are used in many applications due to their high efficiency, high torque density, and compact sizes, which make this type of motors more popular over the other types. This research work focused on torque improvement of PM brushless DC motors by minimizing the generated torque ripples during the commutation period. The approaches and methods adopted in this project are presented thoroughly, along with the mathematical analysis and Matlab-Simulink modeling. Torque ripples in PM brushless DC motor drives usually originate from the motor design structure and from the control side in the form of current ripples.